Water Table Measurement and Monitoring for Flatwoods Citrus - Brian Boman; Thomas Obreza (EDIS)
This is Circular 1409, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002.